Measuring and monitoring biological diversity : standard methods for amphibians - Heyer, W. Ronald (Washington : Smithsonian Institution Press, 1994)
As the Earth's number of species decreases, biologists have been concerned particularly with general decline in amphibian populations, viewing them as particularly sensitive indicators of the health of the environment. Yet one of the most difficult problems in conservation biology is the lack of baseline data against which to measure population changes. Measuring and Monitoring Biological Diversity is the first book to provide comprehensive coverage of standard methods for biodiversity sampling of amphibians, with information on analyzing and using data that will interest biologists in general. In this manual, nearly fifty herpetologists recommend ten standard sampling procedures for measuring and monitoring amphibian and many other populations. The contributors discuss each procedure, along with the circumstances for its appropriate use. In addition, they provide a detailed protocol for each procedure's implementation, a list of necessary equipment and personnel, and suggestions for analyzing the data. The data obtained using these standard methods are comparable across sites and through time and, as a result, are extremely useful for making decisions about habitat protection, sustained use, and restoration - decisions that are particularly relevant for threatened amphibian populations.
Introduction -- Amphibian diversity and natural an overview -- Essentials of standardization and quantification -- Research design for quantitative amphibian studies -- Keys to a successful project: associated data and planning -- Standard techniques for inventory and monitoring -- Supplemental approaches to studying amphibian biodiversity -- Estimating population size -- Analysis of amphibian biodiversity data -- Conclusion and recommendations -- Handling live amphibians -- Techniques for marking amphibians -- Recording frog calls -- Preparing amphibians as scientific specimens -- Collecting tissue for biochemical analysis -- Vendors -- Table of random numbers history
Includes bibliographical references : (page 329-350) and index.
Keywords: Amphibian surveys -- Methodology; Amphibians -- Monitoring; Biodiversity -- Measurement; Biodiversity -- Monitoring